2022
DOI: 10.1186/s12974-022-02659-9
|View full text |Cite
|
Sign up to set email alerts
|

Models of microglia depletion and replenishment elicit protective effects to alleviate vascular and neuronal damage in the diabetic murine retina

Abstract: Microglia, the resident phagocytes of the retina, are believed to influence the development of retinopathy, but their exact contributions to vascular integrity and neuronal loss are unknown. Therefore, utilizing two models of microglia depletion, we aimed to deplete and repopulate microglia to clarify the contribution of microglia to neuronal loss and vascular damage in the diabetic retina in an STZ-induced model of hyperglycemia. Here, we report that 2 weeks exposure to diphtheria toxin (DTx) in diabetic CX3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
(64 reference statements)
3
22
0
Order By: Relevance
“…In addition to a heightened proinflammatory response in diabetic CX3CR1 -KO mice, previous studies showed that CX3CR1 -KO microglia display a gene signature of premature ageing, with an increased expression of proinflammatory genes under naïve conditions that is further amplified with LPS treatment ( 45 ). We recently reported that transient microglia depletion and repopulation utilizing the genetic CX3CR1 CreER :R26 iDTR model of microglia depletion prevented NeuN + RBPMS + retinal ganglion cell and TUJ1 + axonal loss and alleviated vascular damage in the diabetic retina ( 26 ). This study revealed that in mice that retain functional CX3CR1-FKN signaling, microglia can be reprogrammed to be protective in the diabetic retina ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to a heightened proinflammatory response in diabetic CX3CR1 -KO mice, previous studies showed that CX3CR1 -KO microglia display a gene signature of premature ageing, with an increased expression of proinflammatory genes under naïve conditions that is further amplified with LPS treatment ( 45 ). We recently reported that transient microglia depletion and repopulation utilizing the genetic CX3CR1 CreER :R26 iDTR model of microglia depletion prevented NeuN + RBPMS + retinal ganglion cell and TUJ1 + axonal loss and alleviated vascular damage in the diabetic retina ( 26 ). This study revealed that in mice that retain functional CX3CR1-FKN signaling, microglia can be reprogrammed to be protective in the diabetic retina ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that transient microglia depletion and repopulation utilizing the genetic CX3CR1 CreER :R26 iDTR model of microglia depletion prevented NeuN + RBPMS + retinal ganglion cell and TUJ1 + axonal loss and alleviated vascular damage in the diabetic retina ( 26 ). This study revealed that in mice that retain functional CX3CR1-FKN signaling, microglia can be reprogrammed to be protective in the diabetic retina ( 26 ). However, CSF-1R antagonism in diabetic CX3CR1 -KO and hCX3CR1 I249/M280 mice did not alleviate TUJ1 + axonal loss nor vascular damage in contrast to CX3CR1 -WT mice ( Figures 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations